AZF micro-deletion in azoospermia and severe oligospermia: Molecular & histopathological study in Duhok Province - Hanoon, Rana A.; Raziq, Alaa H.; Nerwey, Farida F. (Science Journal of University of Zakho, 2017)
Y chromosome micro-deletion (YCM) is a group of genetic diseases caused by missing gene (s) in specific regions of the Y chromosome. Many individuals with YCM show no manifestations and lead normal life. On the other hand, YCM is known to exist in a significant number of infertile males. Forty adult patients suffering from severe oligospermia and azoospermia were enrolled in the present study. Seminal fluid analyses were performed, and a blood sample was obtained for hormonal analysis and DNA extraction. Follicle stimulating hormone (FSH) and luteinizing hormone (LH) profiles were measured and those who are azoospermic with normal FSH levels were subjected to testicular biopsy. The results revealed that 23 patients were azoospermic while 17 patients were severe oligospermic. It is also shown that ten azoospermic patients had normal serum gonadotrophin levels thus they were directed for testicular biopsy. Histopathological examination of testicular biopsy showed that four patients had obstructive azoospermia while the remaining six suffered maturation arrest. DNA was extracted according to the standard proteinase K/phenol-chloroform method in the medical biotechnology laboratory/Scientific Research Center/University of Duhok. Multiplex PCR was performed for genes located in the azoospermia factor (AZF) regions (AZFa, AZFb, and AZFc) to detect any possible micro-deletions. Y chromosome micro-deletions were determined in 26 patients out of a total of 40 patients. Micro-deletions in the AZFc sub-region appeared in 16 out of 26 patients (61.5 %), and 10 (38.5 %) sample showed AZFb, however, AZFa micro-deletion was not detected in any of the patients. In conclusion, it has been found that Y chromosome micro-deletions in the AZF region can be a determining factor for male infertility and the resultant manifestations.